On invisibilities and blindness: Failures in retrieval of information from books - Amat, Carlos B. (Anuario ThinkEPI, 2008)
The difficulty of gathering information from databases not indexed by search engines is the origin of what is called the deep or invisible Internet. In bibliographic and cataloguing systems, lack of description of book contents leaves users with a kind of blindness. Search technologies are being developed that try to index and provide access to this invisible content. Bibliographic and cataloguing systems, such as ISBN, must take measures to gather and process book contents, particularly specialized texts, and make them accessible to readers. It is proposed that these systems be modified to provide gateways, using protocols similar to Z39.50, that support the capture of book chapters, summaries or synopses of literary works so that the information can be incorporated into the corresponding areas of bibliographic records in online catalogues.
Keywords: Book chapters; Cataloguing; Special libraries.